Evolutionary analysis of DELLA proteins in sweet potato and related species reveals their roles in development and stress responses - Zuo, Zhidan; Zhao, Haoqiang; Fan, Yue; Zhu, Yixuan; Song, Wenpeng; Zhai, Hong; He, Shaozhen; Zhang, Huan; Zhao, Ning; Liu, Qingchang; Gao, Shaopei (Frontiers in Plant Science, 2025)
DELLA proteins act as master negative regulators in the gibberellin signaling pathway, which controls numerous aspects of plant growth and development. Despite the pivotal role of DELLA proteins, a comprehensive genome-wide analysis of the DELLA gene family in sweet potato (Ipomoea batatas) and its related species has yet to be conducted. Here, we performed a comparative analysis of this gene family among six Ipomoea species, including Ipomoea batatas, Ipomoea trifida, Ipomoea triloba, Ipomoea nil, Ipomoea cairica, and Ipomoea aquatica. Among the six Ipomoea species, only I. nil contains five DELLA genes, while the remaining species have three DELLA genes each. The DELLA genes were categorized into three distinct subgroups based on the phylogenetic topology in selected Ipomoea species. Comparative analysis of gene structure and protein motifs revealed that members within the same phylogenetic group exhibit comparable exon/intron and motif organization. The cis-regulatory elements of the DELLA gene in selected Ipomoea species contain unique promoter elements, indicating the presence of species-specific regulatory mechanisms. A multitude of shared cis-regulatory elements related to stress responses were identified in the DELLA gene promoters. Furthermore, a syntenic analysis indicates two groups of syntenic DELLA genes have undergone several rearrangements. The results of the duplication analysis indicated that dispersed duplications contribute to the expansion of the DELLA genes. Moreover, the DELLA genes in sweet potato display an expression pattern that tends to control the growth and development of either the aerial or below-ground parts, and they are responsive to a range of hormones and abiotic stresses. Thus, these findings provide insights into the evolutionary history of DELLA genes within the genus Ipomoea and the functions of sweet potato DELLA genes.